Antioxidant Activities and Caffeic Acid Content in New Zealand Asparagus (Asparagus officinalis) Roots Extracts - Abbey Symes; Amin Shavandi; Hongxia Zhang; Isam A. Mohamed Ahmed; Fahad Y. Al-Juhaimi; Alaa El-Din Ahmed Bekhit (MDPI AG, 2018)
Asparagus officinalis are perennial plants that require re-planting every 10–20 years. The roots are traditionally mulched in the soil or treated as waste. The A. officinalis roots (AR) contain valuable bioactive compounds that may have some health benefiting properties. The aim of this study was to investigate the total polyphenol and flavonoid contents (TPC and TFC, respectively) and antioxidant (2,2-diphenyl-1-picrylhydrazyl (DPPH), Oxygen Radical Absorbance Capacity (ORAC) and Ferric Reducing/Antioxidant Power (FRAP) assays) activities of New Zealand AR extract. The antioxidant activity decreased with a longer extraction time.